A new layer of degradation mechanism for PR-Set7/Set8 during cell cycle. Issue 22 (16th November 2016) - Zheng, Nana; Dai, Xiangpeng; Wang, Zhiwei; Wei, Wenyi
ABSTRACT: Set8 is critically involved in transcription regulation, cell cycle progression and genomic stability. Emerging evidence has revealed that E3 ubiquitin ligases such as CRL4 cdt2 and SCF Skp2 regulate Set8 protein abundance. However, it is unclear whether other E3 ligase(s) could govern Set8 level for proper cell cycle progression in response to genotoxic stress such as UV irradiation. Recently, we report that the SCF β-TRCP complex regulates Set8 protein stability by targeting it for ubiquitination and subsequent degradation. Notably, Set8 interacts with the SCF β-TRCP E3 ligase complex. We further revealed a critical role of CKI in SCF β-TRCP -mediated degradation of Set8. Mechanistically, CKI-mediated phosphorylation of Set8 at the S253 site promotes its destruction by SCF β-TRCP . Importantly, SCF β-TRCP -dependent Set8 destruction also contributes to the tight control of cell proliferation and cell cycle progression, in response to UV irradiation. Here, we summarize our new findings regarding the crucial role of β-TRCP in CKI-mediated Set8 degradation, which could provide new evidence to support that dysregulation of a tight regulatory network of Set8 could lead to aberrant cell cycle process.